Image watermarking based on adaptive models of human visual perception - Khawne, Amnach; Hamamoto, Kazuhiko; Chitsobhuk, Orachat (My University, 2010)
This paper proposes a digital image watermarking based on adaptive models of human visual perception. The algorithm exploits the local activities estimated from wavelet coefficients of each subband to adaptively control the luminance masking. The adaptive luminance is thus delicately combined with the contrast masking and edge detection and adopted as a visibility threshold. With the proposed combination of adaptive visual sensitivity parameters, the proposed perceptual model can be more appropriate to the different characteristics of various images. The weighting function is chosen such that the fidelity, imperceptibility and robustness could be preserved without making any perceptual difference to the image quality. © 2010 The Institute of Electrical Engineers of Japan.
Keywords: Contrast sensitivity function; Human visual system; Image watermarking; Just noticeable difference